ANALISIS KEANEKARAGAMAN GENETIK TIGA POPULASI MATOA (Pometia pinnata Forst & Forst) BERDASARKAN PENANDA RAPD (Random Amplified Polymorphic DNA) - Dwi Wulan; Dewi Indriyani Roslim; Adiwirman (UIR Press, 2024)
Matoa is a plant belonging to the Sapindaceae family, commonly found in tropical regions such as Indonesia. It produces fruit that is renowned for its unique flavor, which is a delightful blend reminiscent of longan, rambutan, and durian, giving it significant economic value. The skin of the matoa fruit comes in various colors, including yellow, green, red, and purple. This study aims to evaluate the genetic diversity among three matoa populations using RAPD (Random Amplified Polymorphic DNA) markers. The populations analyzed include three from Kab. Kampar and two from Pekanbaru City, utilizing four RAPD primers in the process. The research involved multiple steps: collecting leaf samples, isolating total DNA, conducting total DNA electrophoresis, amplifying DNA with RAPD markers, electrophoresing the PCR products, scoring the RAPD bands, and analyzing the data. The findings revealed that the four RAPD primers generated a total of 65 DNA bands, with sizes ranging from 250 bp to 3100 bp. The genetic diversity values among the matoa genotypes varied between 8.748% and 16.186%. Clustering analysis based on the four RAPD primers indicated that the tested matoa samples were not distinctly grouped according to the color of their fruit peels or their geographical locations.